Rivalidade entre os polos : a construção discursiva do Conselho Mundial da Água - Espinoza, Rodrigo de Freitas (2016)
This work aims to characterize the discursive production of the World Water Council, an entity created in 1996 in order to set a plataform for the international debate on water. For this task, we will build, from the discourse plan and the socio-historical context, an analysis of the Environment Conferences and Water Conference as well as the documents and reports published by the Council devoted to the subject. Therefore, the methodological procedures adopted are documentary research, literature review and semi-structured interviews. In conceptual level, this research is supported by the post-colonial and decolonial framework. From this perspective, we have as main objective to analyze the possible impacts of colonialism in the discursive production on the environmental issue, especially in arguments built by the Council. We will be guided by the following hypothesis: the contours that characterize the boundaries of environmental issues are guided by a logic of coloniality of being, knowing and power, thus promoting a theme of entrapment in a discriminatory and hierarchical structure of the world.